Determinants of Health Status and Public Policies Implications – Lessons for Romania - Elena TOADER; Bogdan Narcis FIRTESCU; Florin OPREA (Transylvanian Review of Administrative Sciences, 2017)
The primary aim of this study is to assess the actual impact of healthcare public financing on population health status, while controlling for other non-financial health determinants. There are plenty of heterogeneous studies dealing with the negative or positive effects of different products consumption (e.g. sugar, alcohol, tobacco, fruits, vegetables, etc.) on people’s health. Starting from the relevant ones, we kept for our models those non-financial variables with public available data, used as control variables. After performing variable selection, we ranked the actual impact of different public expenditures categories on health status change, using simple and multiple regression fixed-effects techniques on a panel dataset regarding the European members of OECD (ranging from 1970 to 2014).  Our results show that financing preventive care has the strongest positive impact on the health status, followed by auxiliary (ancillary) services. Administrative expenditures for the healthcare system do not have a significant influence, suggesting there is available room to enhance the effectiveness and performance of sanitary institutions management. Our results also show that life expectancy is negatively affected by the consumption of alcohol and sugar, in a decreasing order. These results were then connected with Romanian realities regarding health care financing and people’s consumption habits. In strong connection with our findings and these realities, this study provides, as a final part, a set of policy recommendations useful for Romanian public authorities in designing their policies, as well as for other interested non-governmental actors.